2017
DOI: 10.14238/pi19.11-12.1979.302-7
|View full text |Cite
|
Sign up to set email alerts
|

The Micro Erythrocyte Sedimentation Rate (ESR) Among Chiidren of the Tobacco Plantation Laborers in North Sumatra

Abstract: Ninety-four children of the Tobacco Plantation Laborers of the PTP IX,aged between 2 months and 12 years, were investigated on erythrocyte sedimen tation rate with the micro ESR method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…One of such methods is Micro-ESR method which was first described by Stuart et al 14 This method requires very small quantity of blood (0.2ml) as it employs glass column of 75mm or 230mm in length and 1mm internal diameter. 1,2,[15][16][17] This study observed that usage of Micro-ESR technique provides very good correlation (r=0.9977) with conventional Westergren method. The result accuracy of this method is acceptable.…”
Section: Resultsmentioning
confidence: 89%
“…One of such methods is Micro-ESR method which was first described by Stuart et al 14 This method requires very small quantity of blood (0.2ml) as it employs glass column of 75mm or 230mm in length and 1mm internal diameter. 1,2,[15][16][17] This study observed that usage of Micro-ESR technique provides very good correlation (r=0.9977) with conventional Westergren method. The result accuracy of this method is acceptable.…”
Section: Resultsmentioning
confidence: 89%